Did the Paris Mosque Save Jews?: A Mystery and Its Memory - Katz, Ethan (The Jewish quarterly review, 2012)
The 2011 French feature film Les Hommes Libres brought unprecedented attention to the story of the Grand Mosque of Paris as a haven for Jews during the Holocaust. Many press accounts and even “expert” commentaries on the film conveyed an almost breathless enthusiasm and framed it as an invaluable pedagogical tool. Such reactions frequently blurred the line between dramatic fictionalized history and verifiable historical fact. This accelerated a pattern seen in discussions around the story of the mosque from the time it first garnered interest in the early 1990s. , This article offers the first scholarly analysis of both the collective memory of the mosque’s efforts to save Jews during the Occupation, and the conflicting historical evidence around this story. The article’s first section argues that discussions of the mosque’s history have reached an impasse between mythology and silent disengagement. The author maintains that three binary historical debates have shaped discussion about the mosque. These debates surround the Vichy syndrome, competing myths of Jews in Muslim lands, and Muslims and the Holocaust. The article’s second half attempts to move beyond these debates by turning to the historical record of the mosque’s conduct in Occupied France. It illuminates the seemingly contradictory choices of the mosque and its rector, Si Kaddour Benghabrit. Benghabrit acted as, all at once, an agent of resistance, collaboration, and accommodation. The history and memory of the Grand Mosque during the Occupation offer important new insights on wartime Muslim-French and Muslim-Jewish relations. The article also sheds light on how Jews, Muslims, and broader French society seek to confront the shifting stakes of the Holocaust and the Second World War in the twenty-first century.